Design of Fourth Order Gm-C Low-Pass Filter for Microsensor Readout - Pugazhenthi R; Ananiah Durai S; Nabihah Ahmad (International Journal of Integrated Engineering, 2026)
This paper presents the design and implementation of a fourth-order transconductance-capacitance (Gm-C) low-pass filter for signal conditioning in interface electronics, realized in gpdk 90 nm CMOS technology. The proposed filter employs a tunable OTA-based multi-stage architecture to achieve a 15 MHz cut-off frequency with sharp roll-off, minimal gain error, and reduced pass-band ripple. To enhance stability and common-mode rejection, the OTA integrates both common-mode feed-forward (CMFF) and a modified common-mode feedback (CMFB) circuit. Post-layout simulations demonstrate a cut-off frequency of 15 MHz, a phase margin of 79°, and improved linearity compared to conventional Gm-C designs. These results confirm that the enhanced OTA architecture offers superior tuning capability, robust common-mode suppression, and reliable high-frequency performance. The contribution of this work lies in providing a compact, high-performance solution for analog front-end signal conditioning, representing a significant improvement over existing CMOS Gm-C filter implementations.